Витрати в системі планування маркетингу на підприємстві - Корінєв, В. Л.; Романчук, C. А.; Бойко, С. В.; Korinyev, V.; Romanchuk, S.; Boiko, S.; Коринев, В. Л. (ЦНТУ, 2020)
Визначено проблему планування маркетингової діяльності вітчизняних підприємств та досліджено її особливості. Запропоновано алгоритм процесу планування маркетингової діяльності згідно результатів цього дослідження. Уточнено роль витрат з позиції ціноутворення при маркетинговому плануванні. Обґрунтовано рекомендації по підвищенню ефективності маркетингової діяльності підприємства з урахуванням особливостей формування витрат на виробництво та реалізацію продукції. The problem of planning of marketing activity of domestic enterprises is defined and its features are investigated. An algorithm for the process of planning marketing activities according to the results of this study is proposed. The role of costs from the point of view of pricing at marketing planning is specified. It is established that the key to the success of the enterprise in modern conditions is the planning of its marketing activities, taking into account the peculiarities of the micro and macro environment. It is important for the company to pay attention to reducing marketing risks by reducing the uncertainty of operating conditions and concentration of resources in the most promising areas. Therefore, the company tries to reduce the level of risk in both long-term and short-term, developing and implementing strategic and tactical planning measures.Considerable attention should be paid to the level of costs for production and sales. This will achieve the goals set by the company and will improve the sales of the company's products and increase its profits. It is advisable to conduct a SWOT-analysis of the strengths and weaknesses of the enterprise and apply a matrix of varieties of its strategic business units. In all areas and at all levels of planning the marketing activities of the enterprise requires the preparation and streamlining of decisions about the goals, means and measures that should ensure the production and sale of products that meet existing demand and future consumer needs. With such marketing planning, this will allow the company to decide on its pricing policy in order not to lose old and attract new customers, which will achieve production efficiency and product competitiveness. Определены проблемы планирования маркетинговой деятельности отечественных предприятий и исследованы ее особенности. Предложен алгоритм процесса планирования маркетинговой деятельности согласно результатам этого исследования. Уточнена роль затрат с позиции ценообразования при маркетинговом планировании. Обоснованы рекомендации по повышению эффективности маркетинговой деятельности предприятия с учетом особенностей формирования затрат на производство и реализацию продукции.
Costs in the Marketing Planning System at the Enterprise
Расходы в системе планирования маркетинга на предприятии
Keywords: маркетинг; планування; ціна; витрати; підприємство; ринкова ситуація; конкуренція; мarketing; planning; price; costs; enterprise; market situation; competition; маркетинг; планирование; цена; расходы; предприятие; рыночная ситуация; конкуренция